The current state of glaciers within the Koryak Highland and assessment of their development by the middle of this century - M. D. Ananicheva (Лëд и снег, 2015)
The Koryak Upland, located in Russian Far East, has so far been poorly studied in terms of glaciology. The information contained in the USSR Glacier Inventory (1982) was obtained by analysis of topographic maps and aerial photography. On the publication date, the Inventory of Koryak Upland included 715 glaciers. To study of the current state of Koryak glaciers, we used satellite imageries – Landsat, Terra /Aqua (EOS AM-1) and ASTER. Deciphering the scenes showed that a significant portion of the glaciers melted away since the mid-1970's until now. We have found only 237 glaciers. Some glaciers are appeared to be rock glaciers, filled with detrital material, cemented by ice in a single body. They might be taken for real glaciers while categorization. The analysis of the retreat (reduction in area) of Koryak glaciers by groups with the same morphological type and the same aspect was conducted. The total retreat of the glaciers of this region varied from 40 (for those measured in situ) to 70% (mean total) as compared to aerial photography surveys (1950). This is the most intense reduction among the studied glacier systems of the Russian Subarctic. It can be explained by the changes in atmospheric circulation due to climate change, the Koryak Upland dries out while the increasing of annual air temperatures. Significant reduction of the glacier area was an incentive for us to undertake a work to assess the evolution of the glaciers in the near future. We used a GCM – ECHAM5 (B1) as the climatic scenario. The projection method has got further development: we have estimated the evolution of glacier systems in which the prevailing type is corries (relatively small circus glacier). The results show a diverse picture of glacier reduction by area, but in general the glacierization will not disappear for the period 2049–2060, reducing the extent by only 17% of the contemporary state.